Exploration for globalizing critical pedagogy in the Korean middle school context: toward critical co-teaching praxis between local and native-English speaking teachers - Byean, Hyera (My University, 2011)
Through this paper, the author highlights the necessity of applying CP in the Korean English educational context on three aspects: to overcome national inferiority attached to the Center English; to maximize students' class participation and improve their linguistic skills and simultaneously critical reflections; to surmount washback effect or teaching to the test through a systematic change. Additionally, the author introduces the general educational concept of critical pedagogy (CP), regarding its historical derivation, meaning, and pedagogical approach of classroom practices and multiculturalism. Applying CP to English language teaching (ELT), the author discusses the implication of English as an international language and its corresponding issue of native-English-speaking teachers vis-a-vis their counterparts, non-native-English-speaking teachers in ELT. After introducing pedagogical principles of CP in ELT and the critical praxis of Wallerstein and Auerbach, a great number of case studies will be illustrated as good examples of CP in ELT. Given the ideological role of English in the Korean context, then, the author will strongly underscore the necessity of CP and its appropriation in the Korean context. In this regard, the author presents the methods of dynamic writing and assessment and appropriate them within the framework of CP in Korea. In the final part of practical classroom practices, the author provides two lesson plans for solo-teaching and two lesson plans for co-teaching respectively, and the co-teaching class will be based on a co-developed syllabus by the negotiation of students and teachers. Along with the visual representation of the classroom procedures, the author elaborates the concise steps of three co-taught classes.
Plan B Paper. 2011. Master of Arts-TESOL--University of Wisconsin-River Falls. English Department. 224 leaves. Includes bibliographical references (leaves 212-224).
Keywords: English language teaching; Critical pedagogy--Korea; English language--Study and teaching--Korea; TESOL; Critical pedagogy; Education--Korea